Jewish Privileges in the Polish Commonwealth. Charters of Rights Granted to Jewish Communities in Poland-Lithuania in the Sixteenth Centuries - Lesiński, Bogdan (Czasopismo Prawno-Historyczne, 1987)
Recenzja: Jacob Goldberg (ed.), Jewish Privileges in the Polish Commonwealth. Charters of Rights Granted to Jewish Communities in Poland-Lithuania in the Sixteenth to Eighteenth Centuries, Jerusalem 1985, ss. XXVI + 477 + mapa + rés. w języku hebrajskim.